1985
DOI: 10.1093/oxfordjournals.jbchem.a135036
|View full text |Cite
|
Sign up to set email alerts
|

β-D-Glucosidase from Seeds of Japanese Cycad, Cycas revoluta

Abstract: beta-D-Glucosidase was purified from seeds of Japanese cycad by dialysis, chromatography on CM-Sepharose CL-6B, gel filtration on Biogel P-200, and chromatofocusing. By chromatofocusing, beta-D-glucosidase was separated into four components whose isoelectric points were in a very narrow range (7.43-7.68). All these components were glycoproteins. The main component (pI = 7.59) was homogeneous on gel isoelectric focusing, and was crystallized from ammonium sulfate solution. The molecular weight of the crystallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…We are analyzing transglucosylation· of f3-D-glucosidase from cycad seeds, using a crystalline enz~me preparatjon. 9 ) In the course of the study, we have found the formation of three new trisaccharide-azoxyglycosides from some azoxyglycosides. This paper deals with the structures of these azoxyglycosides and the mechanism of their formation.…”
Section: Several Neocycasinsmentioning
confidence: 93%
See 1 more Smart Citation
“…We are analyzing transglucosylation· of f3-D-glucosidase from cycad seeds, using a crystalline enz~me preparatjon. 9 ) In the course of the study, we have found the formation of three new trisaccharide-azoxyglycosides from some azoxyglycosides. This paper deals with the structures of these azoxyglycosides and the mechanism of their formation.…”
Section: Several Neocycasinsmentioning
confidence: 93%
“…9 ) One unit of enzyme activity was defined as the amount of enzyme which hydrolyzed 1pmol of o-nitrophenyl j1-D-glucopyranoside in 0.1 M acetate buffer, pH 5.0, at 30°C.…”
Section: Methodsmentioning
confidence: 99%
“…It is reported for the seeds to possess profound anticancer activity against colon cancer [11]. The plant contains several important chemicals including dihydroamentoflavone glucosides [12], peptides [11], chitinase [13], mannose-specific lectins [14], and beta-D-glucosidase [15]. C. revoluta has been reported to have many pharmacological effects such as antioxidant [16], anti-inflammatory, anticancer, antileishmaniasis [12], and antimicrobial [11].…”
Section: Introductionmentioning
confidence: 99%
“…Glucoamylase of Rhizopus niveus hydrolyzed the compound to yield cycasin and glucose (I : I, molar ratio) but fJ-D-glucosidase from cycad seeds 10 ) did not. Furthermore, serial enzymatic hydrolysis of the compound with glucoamylase and cycad fJ-D-glucosidase gave MAM and glucose (1 : 2, molar ratio).…”
mentioning
confidence: 99%